Comparison of treatment durations before Covid-19 pandemic, pre- and post-vaccination periods in acute ischemic stroke patients in a Turkish tertiary hospital - VURAL, EZGİ; ERDEM, SEMA NUR; IRMAK, SEÇİL; MİDİ, İPEK (My University, 2023)
Objective: This study aimed to compare the frequency of admission to hospital in patients with acute ischemic stroke before the COVID 19 pandemic, during the pre-vaccination period, and after the start of vaccination for COVID 19, and to evaluate the time window period between symptom onset to door time, door to CT scan time, door to needle time, and door to puncture time. In addition, it aimed to investigate the effects of the COVID-19 pandemic on the admission, evaluation, and initiation of acute treatment of patients with acute ischemic stroke. Methods: Patients presenting with acute ischemic stroke between March 2019-December 2019 (pre-pandemic), March 2020-December 2020 (pre-vaccination pandemic period), and March 2021-December 2021 (post-vaccination pandemic period) were included in the study. NIHSS was calculated by accordance with the neurological examination findings of the patients, cranial CT for the exclusion of bleeding and CT angiography images for the large vessel occlusions were performed, and the vital signs of the patients were recorded. IV tPA treatment was applied within the first 4.5 hours, and mechanical thrombectomy (MT) was performed in patients with large vessel occlusion. Results: Three hundred nineteen patients were included in the study. The times from symptom onset to emergency admission and from symptom onset to CT scan were found to be similar in all periods. The time from symptom onset to examine by a neurologist was found to be significantly longer in the vaccination period compared to the pandemic period. It was observed that the time from the door to needle time and the time from examine by a neurology doctor to needle time was statistically significantly shorter during the pandemic period (p<0.05). Conclusion: In our study in a tertiary hospital in Turkey, it was determined that the number of patients who was admitted with acute stroke clinic during the pandemic period was similar to other years and there was no delay in the initiation of treatment during the pandemic period. Door to needle times, as well as the time taken by the neurologist to examine and initiate IV-tPA treatment, were found to be shorter in the pre-vaccination pandemic period than in the pre-pandemic and post-vaccination periods.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Neurology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; CLINICAL NEUROLOGY; Yaşam Bilimleri; Nöroloji (klinik); Life Sciences; Neurology (clinical); Acute stroke; COVID-19; IV-tPA; mechanical thrombectomy; pandemic